Interleukin-7 Resensitizes Non-Small-Cell Lung Cancer to Cisplatin via Inhibition of ABCG2. (14th December 2019) - Ke, Bin; Wei, Ting; Huang, Yuanyuan; Gong, Yuxin; Wu, Gang; Liu, Junfang; Chen, Xiaoting; Shi, Lin
Abstract : Treatment with cisplatin (DDP) is one of the standard therapies used to treat non-small-cell lung cancer (NSCLC) and fundamentally causes resistance in cancer cells, which eventually poses as an obstacle to the efficacy of chemotherapy in NSCLC. Efforts are on all over the world to explore a sensitizer of NSCLC to DDP. Here, we studied the effect of IL-7 on the resistance of NSCLC to chemotherapy. We observed that IL-7 treatment significantly enhanced DDP-induced effects in A549 and A549/DDP cells (DDP-resistant cells), including decreased cell viability and proliferation, as well as increased cell apoptosis and S arrest, indicating that IL-7 treatment resensitized DDP-resistant NSCLC cells to DDP. Subsequently, IL-7 enhanced the sensitivity of PI3K/AKT signaling and expressions of ABCG2 to DDP. By inhibiting IL-7 signaling via IL-7R knockdown or activating PI3K/AKT signaling via PI3K activation, the resensitization to DDP by IL-7 was abrogated, and the expression levels of ABCG2, p-PI3K, and p-AKT were found to be significantly higher. In vivo results also confirmed that IL-7 only in combination with DDP could remarkably induce tumor regression with reduced levels of ABCG2 in tumorous tissues. These findings indicate that IL-7, apart from its adjuvant effect, could overcome multidrug resistance of DDP to restore its chemotherapy sensitivity.